The fishbowl. A Critical reflection between teachers and Master's students in two interactive LS plans. An experience at the University of Malaga. - Soto-Gómez, Encarnación; Pérez-Gómez, Ángel Ignacio; Servan-Núñez, María José (My University, 2023)
Purpose- The paper aims to present the experience of convergence between two simultaneous and interactive processes of LS development in a Master of Educational Innovation at the University of Malaga in Spain. Design- Case study of an educational experience in the University context. It involves a group of 30 students, two subjects and 3 teachers. Description: The first version of the experience began 10 years ago (Soto, Serván and Pérez, 2015) Three years ago, the three lecturers set out to incorporate LS as a structure for this task in order to stimulate the development of critical thinking and to improve the tutoring of this work, developing our own teaching task as an explicit LS process. Findings: Among the most significant findings of this dual, parallel and interactive LS process, we can highlight: - The substantive increase in motivation of both students and teachers. - The complexity of integrating and harmonising the roles of observation-inquiry and teaching-by the students and, in the case of teachers, increased by the need to evaluate the learning process developed by the students themselves. - The extraordinary influence of what we have called the fishbowl effect. That is to say, the linking of the two final phases of the LS, placing themselves in the centre of the circle and openly exposing their perception of the weaknesses and strengths of their LS process, has stimulated a powerful simultaneous process of reflection and critical self-evaluation among the components of the small group, which has been strengthened by the final presentation of the teachers' reflections on their own LS. Relevance: The importance of generating simultaneous and interactive LS processes between teachers and students in initial teacher training. Especially the teachers' fishbowl effect, for their strong modeling influence, is so relevant that it appears in all student’s portfolios as one of the most impacting models for their teacher education process.
The paper aims to present the experience of convergence between two simultaneous and interactive processes of LS development in a Master of Educational Innovation at the University of Malaga in Spain to stimulate the development of critical thinking in education.
Keywords: Profesores - Formación profesional; Enseñanza - Innovaciones; Enseñanza superior; Lesson study; Practical knowledge; Teacher education